Stasiun Kerja Komputer Secara Ergonomis Untuk Kegiatan Belajar Di Kelas Gempur Santoso - Santoso, Gempur (WAKTU, 2011)
Currently very rapid development of computers. In the world of education was not freefrom the use of computers for education and administration activities in the classroom learningprocess. Computers connected to the equipment of information technology (IT) the other tosimplify and speed up the store and get information. Stout incident if the station is notergonomically designed computer it will cause slowness, fatigue, even pain. In this paper willdiscuss the ergonomic computer workstations in the classroom for learning activities that studentsand teachers do not have an accident. Additionally, it will also describe the incidence of accidentsdue to ergonomic display that does not impact cause slowness, fatigue, even illness or accident.Analysis and discussion in this paper presented in a descriptive or commonly called the study ofliterature. Based on the discussion can be concluded that an important factor in addition to thedesign of the workstation-related anthropometry students and teachers, are also factors thatadequate lighting and no glare, radiation and glare on the monitor as much as possible avoidedwith anti-glare or use an LCD, the corresponding input devices, peripherals, and softwareperformance and hardware. Suggestion: structuring computer display in the classroom should beergonomic is designed to be comfortable and secure in teaching and learning activities.